Sertifikasi Tanah Program Pendaftaran Tanah Sistematis Lengkap: Deskripsi dan Manfaatnya - San Yuan Sirait; Muhammad Nazer; Busyra Azheri (BHUMI: Jurnal Agraria dan Pertanahan, 2020)
To improve land registration in Indonesia, the government is determined to register all land in the territory of the Republic of Indonesia no later than 2025 through a land program which is primarily the Complete Systematic Land Registration (PTSL). This research is a survey research that aims to describe the benefits and implementation of the PTSL land certification program in Bintan Regency. The survey results show that there are several main benefits of the PTSL land certification program that are felt by the community, including providing a sense of security over land, changes in land use that are more useful, and increasing land value. In its implementation, land certification through the PTSL program is  considered easy by the community. However, community participation in extension is still low, which results in low understanding of the participant about the land certification process and its benefits in their lives. There are still people who do not take care of their own land certificates in the PTSL program.Keywords: PTSL, Security, Land Value, Land Use. Intisari: Untuk mempercapat pendaftaran tanah di Indonesia, pemerintah bertekad untuk mendaftarkan seluruh tanah di wilayah Republik Indonesisa paling lambat tahun 2025 melalui program pertanahan yang utamanya Pendaftaran Tanah Sistematis Lengkap (PTSL). Penelitian ini merupakan penelitian survei yang bertujuan untuk mendeskripsikan manfaat dan implementasi sertifikasi tanah program PTSL di Kabupaten Bintan. Hasil survei menunjukkan terdapat beberapa manfaat utama dari sertifikasi tanah program PTSL yang dirasakan oleh masyarakat, yaitu memberi rasa aman atas tanah, perubahan penggunaan tanah yang lebih bermanfaat, dan peningkatan nilai tanah. Pada implementasinya, proses pengurusan sertifikat tanah melalui program PTSL dianggap mudah oleh masyarakat. Namun, keikutsertaan warga dalam penyuluhan masih rendah, yang mengakibatkan rendahnya pemahaman masyarakat tentang proses sertifikasi tanah dan manfaatnya dalam kehidupan mereka. Masih terdapat masyarakat yang tidak mengurus sendiri sertifikat tanahnya pada program PTSL.Kata Kunci: PTSL, Rasa Aman, Nilai Tanah, Perubahan Penggunaan Tanah.